Energy Management System without using Battery Bank - Mrs. Ramya M, Mrs. Divya N S, Dr. Nagaraj H P,Mrs. Rekha S N, Mrs. Ashwini A V, Mrs. Jhansi K (International Journal of Advanced Science and Technology, 2020)
The usage of Solar energy is counting to growth at a rapid rate due to the increasing energy demand and a constant depletion in fossil fuels. In decentralized Solar PV Power Plants, conventional batteries are used as energy storage devices. In these cases, shorter life span of the batteries results in frequent replacement of components which increases the operating cost and disposal of used batteries contributes to hazardous waste and pose threats to health and environment. This paper proposes to utilize the Hybrid Ultra Capacitors as an energy storage device to increase the battery life and further development in storage technology can promote HUC as a replacement of batteries in times to come.